Understanding the dramatic therapeutic play session: a contribution to pediatric nursing - Vera Lucia Alves dos Santos; Fabiane de Amorim Almeida; Carina Ceribelli; Circéa Amália Ribeiro
ABSTRACT Objectives: to understand how the dramatic therapeutic play session occurs within the care of hospitalized children. Methods: qualitative multiple case study, using theoretical references, such as symbolic interactionism and Vygotsky's theory of symbolic play. Twenty play sessions performed with six children from 3 to 10 years old were analyzed, each corresponding to one case. Results: these sessions demonstrated that a dramatic therapeutic play session is a process of four interdependent and complementary steps: bonding, exploring, dramatizing, and play cessation. They also revealed the imaginary situations externalized by the child, the importance of the exploration step for which they manage the imaginary situation and catharsis, and how her higher psychological faculties are articulated during this process. Final Considerations: the results contribute to the understanding of the conduct and analysis of the dramatic therapeutic play session, reinforcing the importance of its use in pediatric nursing care practice.